Academician of the National Academy of Sciences of Ukraine Vadym Loktev (to his 80th birthday) - Brizhik, Larissa (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
Dear Reader, You open the special issue of the Low Temperature Physics journal, dedicated to 80 years of outstanding Ukrainian physicist-theorist Vadym Loktev. Doctor of Science in Physics and Mathematics, Professor, Honored Worker in Science and Engineering of Ukraine, Laureate of two State Prizes of Ukraine, Academician of the National Academy of Sciences of Ukraine (NASU), a member of the Presidium of the NASU, Academician-Secretary of the Department of Physics and Astronomy of the NASU.